Diabetic nephropathy in type 2 diabetes: The frequency and risk factors - Maksim Kovačević; Nenad Petković; Marijana Kovačević; Snežana Mališ; Verica Prodanović; Olivera Čančar; Siniša Ristić; Ljubica Djukanović (Биомедицинска истраживања, 2019)
Introduction: The aim of the study was to determine the frequency and risk factors for diabetic nephropathy (DN) in patients with type 2 diabetes as well as the factors related to kidney function decrease over a three-year period. Methods: The study involved 81 patients with type 2 diabetes, initially classified into two groups: the first group was comprised of 41 patients with DN (27 males; 62.03 ± 7.73 years) while the second one included 40 patients without DN (17 males, 61.73 ± 11.55 years). All of them were subjected to history taking, objective examination as well as laboratory examination. Based on the results of the study lasting for three years, the patients of both groups were divided into subgroups with stable kidney function and subgroups with impaired kidney function, defined as an increase in proteinuria level and/or decrease in estimated glomerular filtration rate (eGFR) by more than 25%. Results: In both groups, high incidence rates of known risk factors for diabetes and DN were recorded at the beginning of the study. The multivariate logistic analysis identified the female sex and the duration of diabetes as significant predictors of DN. After three-year period, kidney function declined in approximately 50% of patients with and without DN. Furthermore, the values of fasting glycemia and HbA1c were statistically higher in the groups with impaired kidney function compared to the ones with stable eGFR. The linear regression analysis revealed that, during three-year period, the change in eGFR was significantly associated with patient age, the duration of diabetes, systolic blood pressure, the difference in diastolic readings and proteinuria. The change in proteinuria was strongly associated with systolic blood pressure, the difference in diastolic readings, as well as with HbA1 and eGFR at the end of the study. Conclusion: In patients with type 2 diabetes, female sex and longer duration of diabetes were identified as significant risk factors for DN, while patient age, the duration of diabetes, elevated blood pressure and poor glucoregulation were identified as risk factors for kidney function decrease.
Keywords: diabetic nephropathy; proteinuria; glomerular filtration rate; risk factors